Phonological Analysis of Arabic Language Linguistic Review Ferdinand De Saussure - Ahad Hilman Fattaya (Budapest International Research and Critics University, 2022)
This research was conducted on the basis of an important role related to the re-analysis of Arabic phonology because language and human life are two inseparable phenomena. The emergence of a modern view of language known as modern linguistic theory in the 19th or early 20th century made the world of linguistics not only focus on traditional linguistic theory. Arabic has a sound with its own meaning, so sound errors can lead to misinterpretations. The existence of structural theory made an update on studies related to linguistics and then gave rise to the figure of Ferdinand De Saussure who is known as the